Mining and metallurgical tradition in the Spis region and its reflection in the hydronymia of the Hornád River basin - Goótšová, Andrea (Geographical names in physical space, 2016)
The paper draws attention to an attempt to clarify a long-lasting tradition of mining and metallurgy in the Spis region. Taking into account the arrival of German miners and metallurgists and the background of a historical development, the names of water streams in the Smolnik and Hnilec valley are being described. The professional terminology related to their activities which left its impact on hydronyms have become the subject of our analysis.